EVALUASI DESAIN SISTEM PERENCANAAN DAN PENGENDALIAN MANAJEMEN UNTUK MENGHADAPI MASYARAKAT EKONOMI ASEAN TAHUN 2015 - Sunardi, Sunardi; Djazuli, Abid (Benefit: Jurnal Manajemen dan Bisnis, 2015)
The ASEAN Economic Community by 2015, there will be five free flow are: flow of goods, services ,investment flows, flows of capital and labor flows, the condition creates opportunities and challenges for companies in Indonesia, so the company needs to prepare a strategic move . Competitiveness of the Indonesian nation needs to be improve , in order to be able to compete with the ASEAN countries Assess the design of management planning and control system (SPPM) should be done . SPPM structure comprisin : ( a) the organizational structure is designed using the system ownership approach ( cellular manufacturing system, just-in -time purchasing and production, customer-driven innovation, and customer service focus. (b ) networking organization , is done by the development of information technology ( information technology and transaction processing technologies of information processing ) , and (c) reward system , giving awards to personnel based on performance , with the implementation of the balanced scorecard on the other hand SPPM process comprising: (a) the design must be done through the formulation of strategies trendwatching, SWOT analysis , envisioning and choosing strategies , (b) the design of structured strategic planning by determining the vision , mission , goals , strategies , basic beliefs and basic values , (c ) the design of programming , with outlines strategic initiatives into the program (d ) design approach to budgeting is done with activity-based budgeting (e) implementation of management focus on the management of the activity and ( f ) the monitoring is done by